Strategi Guru Dalam Membangun Motivasi Belajar Siswa - Solin, Wardah; Angraini, Wilda; Fitriani, Fitriani; Paujiah, Nurmaulida; Andani, Dewi; Yuris, Evi Cenna (EL-EMIR Institute, 2025)
Learning motivation is one of the essential aspects of the educational process, as it influences the extent to which students are actively and enthusiastically engaged in learning activities. Without strong motivation, students' potential will not develop optimally and may even result in low academic achievement. In this context, teachers play a strategic role as facilitators and motivators who are capable of creating a learning environment that encourages students’ enthusiasm. This study aims to identify and describe various effective strategies that teachers can use to enhance students’ learning motivation in schools. The findings indicate that strategies that are relevant and aligned with students' characteristics need to be carefully selected to ensure the learning process is meaningful and engaging. Moreover, creating a positive learning environment will strengthen emotional connections, a sense of security, and a spirit of collaboration, all of which contribute to increased motivation. By implementing these three approaches in an integrated manner, teachers can create a learning climate that supports students’ optimal and sustainable development.